Sensory Product SENSORY PROPERTIES AND CONSUMER ACCEPTANCE OF THEM BANANA AMBON (Musa paradisiaca var. sapientum (L.) Kunt) USING FOOD DEHYDRATOR INFLUENCED BY DRYING TIME - Lomo, Christine Phaskalyena (Program Studi Teknologi Hasil Pertanian, Politeknik Gorontalo, 2024)
Ambon bananas are a fruit that is widely consumed by people. Apart from being easy to obtain,Ambon bananas are rich in vitamin A, compared to other types of bananas. Ambon bananas alsocontain nutrients such as carbohydrates, vitamins, minerals and high levels of potassium. Ambonbananas are also widely liked by Indonesian people because they have a sweet taste and softtexture. Apart from being fresh fruit, Ambon bananas are often processed into various productssuch as chips, jam and other snacks. One processing method that can extend the shelf life ofbananas is drying which produces dried fruit. Using a dryer can speed up the drying process andalso ensure a better level of cleanliness compared to drying done in the sun. A food dehydratoris a drying tool that functions to dry food ingredients by removing the water content containedin the ingredients. Dried fruit is fruit that is processed by drying it under direct sunlight or usingtechnology, namely an artificial drying device (oven or dehydrator) but still retains its taste andaroma. Dried fruit can be preserved longer than fresh fruit and can be a practical snack, especiallyto satisfy hunger. This research aims to examine the effect of drying time with a food dehydratoron sensory properties or level of liking using the hedonic organoleptic test, determine the watercontent using the oven method, determine the total sugar using a refractometer, and determinethe ash content in dried Ambon banana fruit. Analysis results: Drying Ambon bananas using afood dehydrator with a drying time of 12 hours at a temperature of 60oC provides optimal resultsfor sensory properties (color, texture and taste). And produces quite good chemical content. Thewater content of dried Ambon banana fruit ranges from 5.003 to 1.512